The Relationship Between Knowledge and Attitudes Toward Sexually Transmitted Infections and Adolescent Sexual Behavior: Hubungan Pengetahuan dan sikap tentang Penyakit Menular Seksual dengan Perilaku Seksual Remaja - Destariyani, Elvi; Yuniarti; Sholihat, Suci (JURNAL KEBIDANAN, 2025)
Prevalence of sexual behavior in children, around 15% of women under the age of 18 gave birth globally in 2015-2020 and 90% or more of these births occurred in developing countries. The prevalence of having had sexual intercourse in Indonesia is 60% in adolescents aged 16-17 years, 20% in adolescents aged 19-20 years and 20% in adolescents aged 14-15 years. This study is to analyze the relationship between knowledge and attitudes about sexually transmitted diseases with adolescent sexual behavior. This study is an analytical survey study with a cross-sectional method. The study was conducted at SMAN 1 Kota Bengkulu with a population of 190 class X female students with a sample calculated using the Slovin formula, a research sample of 105 people was obtained using a multiple technique. The data was analyzed using the Chi Square test. The results showed that some respondents had less knowledge about STDs, most had negative attitudes and a small number had high-risk sexual behavior. There is a relationship between knowledge and about sexually transmitted diseases with adolescent sexual behavior p value = 0.002 and adolescent attitudes about STIs with adolescent sexual behavior p value = 0.028. It is expected that health workers can coordinate with the Health Center and PKBI in order to design and develop programs for health education related to adolescent sexual behavior.